The reinstatement of the jury system in Malaysia: an analysis / Muhd Nasrul Wajdee Mohd Nasir ... [et al.] - Mohd Nasir, Muhd Nasrul Wajdee; Mior Shaifiiddin, Mior Muhammad Fadhli; Azanam Shah, Nor Aqila; Yazid, Hanaq; Hilaluddin, Fatin Saiha (2010)
This project attempts to identify the reasons behind the abolishment of the jury system and also to identify a way to overcome the weaknesses in our judicial system. The data of this research paper were gathered through interviews. With this research paper, we would be able to see whether the reinstatement of jury system might overcome the problem in our judiciary system. Therefore, the aims of our study are to explore the jury system and our judicial system to see whether there is a possibility to reinstate the jury system in Malaysia. The first chapter in this research provides the introduction of our draft proposal in conducting this research. The next chapter provides the discussion of various aspects regarding the jury system and the judge system including the strengths and weaknesses of each system Chapter three further provides the history of the jury system in Malaysia since the time the Charter of Justice was introduced. This chapter discusses the history of Malaysia till the time our country decided on the abolishment of the jury system. Furthermore, the fourth chapter provides the study on the modes of trials implied in other countries where we have identified a country which has already abolished the jury system, a country which has revived the jury system and also a country which is still using the jury system. The chapter may provide on the reasons why a particular country is implementing that certain legal system. Lastly, chapter five provides findings and chapter six provides the recommendations and conclusions of this research paper. The issue of the jury system is still being debated throughout the whole world and for that it is important for our group to analyse all the possible and relevant issues which may later help us in identifying whether or not the jury system should be revived back in Malaysia.